May Measurement Month 2017: an analysis of blood pressure screening results in South Africa—Sub-Saharan Africa. (24th April 2019) - Woodiwiss, Angela J; Kruger, Ruan; Norton, Gavin R; Schutte, Aletta E; Vally, Muhammed; Da Silva Fernandes, Daniel; Masiu, Mohlabani; Kolkenbeck-Ruh, Andrea; Gafane-Matemane, Lebo F; Ahiante, Blessing O; Phalane, Edith; Crouch, Simone H; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative of the International Society of Hypertension (ISH) aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programs worldwide. A surveillance study in 2016 in South Africa revealed that 45% of adults have hypertension and only 6–9% of men and women respectively had controlled BP on medication, highlighting the need for regular screening and awareness campaigns. An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2017. Blood pressure measurement, the definition of hypertension, and statistical analyses followed the MMM protocol. The sites screened were primarily university campuses and general populations in preference to hospitals and clinics, aiming to raise awareness and allow access to screening in those less likely to be aware of their BP. In total, 3250 individuals (mean age 31.0 ± 13.3 years) were screened. After multiple imputation for missing BP readings, 795 (24.5%) had hypertension. Of individuals not receiving antihypertensive medication, 459 (15.7%) were hypertensive, and 157 (46.9%) of individuals receiving antihypertensive medication had uncontrolled BP. These results suggest that opportunistic screening campaigns can identify significant numbers with undiagnosed and uncontrolled hypertension, even amongst the fairly young. The high proportions of individuals with undiagnosed and treated uncontrolled hypertension, highlight the need for campaigns to increase hypertension awareness and control.